Penerapan Keadilan Restoratif dalam Penegakan Hukum Pidana: Studi Kasus di Kepulauan Selayar - Asruddin; Rahman, Sufirman; Razak, Azkari (Sekolah Tinggi Agama Islam Negeri Majene, 2024)
The purpose of this study was to: (1) assess the need for restorative justice to be applied as soon as possible in criminal law enforcement; and (2) assess how restorative justice is regulated when it comes to its use as a substitute for case resolution. This study employs a descriptive qualitative methodology and an empirical law-based research strategy. Data analysis is done using the findings from informant interviews. The findings demonstrated that: (1) Essentially, the Selayar District Attorney's Office's use of restorative justice in the law enforcement process during the settlement of criminal cases can bring justice to the litigants—that is, the criminals, the victims, and any interested parties. Proportionality justice, which offers a balance of interest recovery between the criminal and the victim, is the context of justice within the framework of the restorative justice approach. The victim receives compensation for the losses he sustained as a result of the acts of the offender, and the offender is returned to his pre-crime rights and no longer considered a former offender. Within the jurisdiction of the Selayar Islands District Attorney's Office, a number of factors, including legal substance, legal structure, legal culture, and facilities and infrastructure, have a significant impact on the restorative justice.